2017
DOI: 10.1111/btp.12447
|View full text |Cite
|
Sign up to set email alerts
|

Commonness, rarity, and oligarchies of woody plants in the tropical dry forests of Mexico

Abstract: We assessed woody plant communities in two widely separated forests in the tropical dry forest (TDF) biome of Mexico for evidence of similar patterns of species commonness and rarity. We used belt transects laid out along contour lines (i.e., constant elevation) and stratified across elevation gradients at sites in Jalisco and Oaxaca to sample woody plant species diversity, abundance, relative frequency and basal area. We assembled a combined species list and compared species found in both sites (shared) to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
5
0
3
Order By: Relevance
“…We also found that the most widespread dry forest species were generalists that are favored by forest disturbance and early successional stages (appendix table A2), as reported by previous studies (Uribe et al 2001, López-Camacho et al 2012, Castellanos-Castro and Newton 2015, Williams et al 2017 for other TDFs (Newbold et al 2014), indicating the incipient successional status of dry forests at the regional level (Derroire et al 2016). Furthermore, we found an introduced invasive species (V. farnesiana) among the most common species of TDFs throughout the country, suggesting that TDFs are also highly susceptible to invasion (Pizano et al 2014a).…”
Section: Floristic Distinctiveness Correlates With Environmental Hetesupporting
confidence: 87%
See 2 more Smart Citations
“…We also found that the most widespread dry forest species were generalists that are favored by forest disturbance and early successional stages (appendix table A2), as reported by previous studies (Uribe et al 2001, López-Camacho et al 2012, Castellanos-Castro and Newton 2015, Williams et al 2017 for other TDFs (Newbold et al 2014), indicating the incipient successional status of dry forests at the regional level (Derroire et al 2016). Furthermore, we found an introduced invasive species (V. farnesiana) among the most common species of TDFs throughout the country, suggesting that TDFs are also highly susceptible to invasion (Pizano et al 2014a).…”
Section: Floristic Distinctiveness Correlates With Environmental Hetesupporting
confidence: 87%
“…In fact, environmental and soil factors explained 13% of the variation in plant species composition ( figure 2(c)). Similar to other dry forests in the Neotropics, we found high species turnover for both across and within regions (Linares-Palomino et al 2011, Neves et al 2015, DRYFLOR et al 2016, Williams et al 2017, as well as high levels of endemism across TDF regions. Floristic composition in the Caribbean appears to be correlated with soils with a high pH and high bulk density, high mean annual temperature, and the longest dry season ( figure 2(c)).…”
Section: Floristic Distinctiveness Correlates With Environmental Hetesupporting
confidence: 83%
See 1 more Smart Citation
“…The lowland Isthmus of Tehuantepec, which represents the border between the North American and Central American biogeographical provinces, is influenced mostly by these weather patterns, neotropical climate, and biogeography. As such, the vegetation in these forests is frequently dominated by lineages of South American or Central American‐Caribbean origin (for representative species lists, see Boyle, ; García‐Mendoza & Meave, ; Salas‐Morales, Saynes‐Vasquez, & Schibli, ; Williams, Trejo, & Schwartz, ).…”
Section: Discussionmentioning
confidence: 99%
“…The major temperate and tropical axis vegetation types are projected to experience similar increases in the percentage of their area that shifts into the "high" and "very high" exposure categories in both the near-future (9.5% and 11%, respectively) and end-century (30% and 32%, respectively) periods, based on the five-model average. The differences in the percentage of cells projected to move into the NA category are more striking, with a much higher percentage of NA cells projected for the tropical axis compared to the temperate axis in both the near-future (1.1% vs. 0.067%) and end- Boyle, 1996;García-Mendoza & Meave, 2012;Salas-Morales, Saynes-Vasquez, & Schibli, 2003;Williams, Trejo, & Schwartz, 2017).…”
Section: Discussionmentioning
confidence: 99%